Energy security: its place in the relations between the European Union and Russia - Yakupova, Venera (My University, 2013)
Bu çalışma, Avrupa Birliği ve Rusya arasındaki ilişkileri ‘enerji güvenliği’ konsepti ışığında iki uluslararası ilişkiler teorisi aracıyla analiz etmektedir. Bunu gerçekleştirebilmek için, bu tez şu soruları cevaplamayı hedefler: “Avrupa Birliği ve Rusya ilişkilerinde enerji güvenliği konsepti ne anlama gelir?”, “İki uluslararası ilişkiler teorilerinden hangisi iki aktör arasındaki ilişkileri enerji güvenliği açısından daha iyi ifade ediyor?” Ayrıntılı analiz üç sonuca ulaşmaktadır. İlk olarak, enerji güvenliği enerji tüketicileri, tedarikçiler ve transit ülkelerin arasında entegrasyon ve yakın işbirliği koşulu ile gerçekleşebilir. Çünkü, üç katılımcıdan birinin ihmal edilmesi enerji güvenliğinin gerçekleşmesini engeller. İkinci olarak, Avrupa Komisyon’unun enerji konusunda tam yetkisi bulunmadığından, ve üye ülkelerin ‘birlik ses’inin eksik olması nedeniyle, Avrupa Birliği’nin esas dış enerji politikası söz konusu değildir. Son olarak, tezde gerçekleştiren analiz, enerji güvenliği bakış açısından, bu iki aktörün arasındaki ilişkilerin neorealism ile daha başarılı açıklandığını göstermektedir.

This thesis aims at analysing the relations between the European Union and Russia from the perspective of ‘energy security’ concept by applying the two international relations theories, namely, neorealism and neoliberal institutionalism. In order to accomplish this task, the study targets the following questions: “What does the concept of energy security stand for in the relations between the EU and Russia?”, and “Which theory of the international relations explains the relations between the actors in the light of ‘energy security’ better?” At the end of the thorough analysis, this study reaches three main conclusions. Firstly, energy security is a phenomenon, which can be reached under the condition of the integration and close cooperation between consumers, suppliers and transit countries. If any of the participants is neglected, ‘energy security’ is almost impossible to achieve. Secondly, there is no energy policy of the European Union with external dimension, mainly, due to the lack of single voice between the member states over energy issues, the absence of the European Commission competence in this sphere. Finally, the relations between the two actors in the light of ‘energy security’ concept are better explained by neorealism theory.
Keywords: Avrupa Birliği; Avrupa Birliği Ülkeleri; Dış İlişkiler; Enerji Koruma; Enerji Politikası; Güç Kaynakları; Rusya